Coagulation factors induce human skin mast cell and basophil degranulation via activation of complement 5 and the C5a receptor - Yanase, Yuhki; Matsuo, Yoshimi; Takahagi, Shunsuke; Kawaguchi, Tomoko; Uchida, Kazue; Ishii, Kaori; Tanaka, Akio; Matsubara, Daiki; Ozawa, Koichiro; Hide, Michihiro (Journal of allergy and clinical immunology, 2021)
Because serine proteases, such as coagulation and/or fibrinolysis factors, may convert C5 into C5a and C5b, we investigated the effect of C5 in the presence of factor VIIa, factor Xa, factor IIa, or plasmin on the degranulation of hsMCs. [...]C3 induced a slight degranulation of hsMCs even in the presence of factor Xa and factor IIa (Fig 1, C). [...]nafamostat mesylate, a serine protease inhibitor, reduced C5 plus IIa– and C5 plus plasmin–induced degranulation of hsMCs in a concentration-dependent manner. [...]neither C5 nor the coagulation factors Xa or IIa induced histamine release by themselves, but the combination of C5 and factor IIa or factor Xa did (Fig 2, B). To date, several articles have implied that activated coagulation factors, such as Xa and IIa, directly activate hsMCs via PAR1 or PAR2 in CSU.9 Although we could not rule out the involvement of PARs for mast cell and basophil activation on account of the experiments having a small number of subjects, we demonstrated that C5a resulting from the extrinsic coagulation system induces degranulation of hsMCs and basophils via C5aR. [...]we established an alternative hypothesis of mast cell and/or basophil activation through the coagulation pathway and complement (see Fig E6 in this article's Online Repository at www.jacionline.org).